Решите уравнение: 0,6(у – 3) – 0,5(у – 1) = 1,5. 0,8(х – 2) – 0,7(х – 1) = 2,7.

2

Ответы и объяснения

  • Myauu
  • середнячок
2013-04-10T18:08:12+04:00

 0,6(у – 3) – 0,5(у – 1) = 1,5

0,6у-1,8-0,5у+0,5=1,5

0,6у-0,5у=1,5+1,8-0,5

0,1у= 2,8

у=28

 

 

 

 

 

 

 

 

  • Участник Знаний
2013-04-10T18:09:30+04:00

Раскрываем скобки: Получаем

0.6y-1.8-0.5y+0.5=1.5

0.1y=1.5+1.8-0.5

0.1y=2.8

y=28

Ответ:y=28

Тоже самое :

0,8х - 1,6 - 0,7х + 0,7 = 2,7
0,8х - 0,7х = 2,7 + 1,6 - 0,7
0,1х = 3,6
х = 3,6 : 0,1
х= 36

Ответ x=36

Всё Незачто:)